Struktur dan Fungsi Pantun Pembuka dan Penutup Majlis dalam Adat Melayu - Zia Hisni Mubarak (LPPM Universitas Putera Batam, 2020)
The purpose of this research is to see the structure and function of the opening and closing pantun majlis. This research is a literature review that examines data from the available literature. To analyze pantun, several processes are carried out, such as reading and analyzing the structure and function of pantun. The data are then described qualitatively and interpreted into an understanding of the cultural values of the Malay which are full of moral messages. The data consisted of 16 pantun, 7 opening rhymes and 9 closing majlis. The results showed that the structure of the opening and closing of the majlis rhymes was cross rhymes a-b-a-b consisting of 4 lines where the 2 lines at the beginning were sampiran and the last 2 lines were the contents of the pantun. Each line consists of 3 to 6 words with syllables consisting of 8 to 12 syllables, but there is one pantun content that has 18 syllables. Meanwhile, the values of local wisdom found are based on the function of the pantun which consists of 5 main functions, namely didactive, aesthetic, morality, recreation and religious functions.